Fast convergent double inertial subgradient extragradient algorithm with self-adaptive step size for variational inequalities and fixed point problems in Hilbert spaces - Li, Min; Xie, Zhongbing (Journal of computational and applied mathematics, 2026)
In this paper, we propose a double inertial subgradient extragradient method for solving variational inequalities and fixed point problems in Hilbert spaces. We add a parameter in the second step projection to adjust the step size, thereby increasing the convergence rate of the proposed algorithm. In addition, we make appropriate improvements based on the common self adaptive rules. Finally, through numerical experiments, we not only verify the effectiveness of the added parameters, but also show that our algorithm has better convergence behavior than other known results.